Investigating the D" Reflector Beneath the Indian Ocean with Source Arrays - Thomas, Christine; Heyn, Björn Holger; Tölle, Lena; van Tent, Rûna (Seismica, 2025)
We used seismic P-wave reflections to search for the discontinuity at the top of the D" region beneath the Indian Ocean. Due to a lack of seismic receiver arrays to target this region, we build source arrays using earthquakes in Indonesia and taking advantage of the long-running history of GEOSCOPE stations located in the western Indian Ocean and Antarctica, as well as three additional stations (Seychelles and Antarctica). Despite restricting the earthquake depth range, source-array stacks were difficult to interpret due to complications arising from differing earthquake depths, violating the plane wave assumption. Therefore, we use a source-array scatter imaging method, that does not rely on travel-times calculated for a plane wave. Using this technique in conjunction with source normalization, we found evidence for a D" P-wave reflector for several stations with reflector depths varying between 230-160 km above the CMB South of Australia and 190 to 270 km above the CMB beneath the Indian Ocean, where the depth of the reflector in the north of our study area is consistent with previously imaged D" depths using S-waves and agrees with receiver array data. We suggest that earlier imaged subducted lithosphere in this region is responsible for our D" reflections.